Investigation of clinical parameters associated with COVID-19 in pregnant women - Sharma, Mehak; Kaur, Amandeep; Singh, Kanwardeep; Sidhu, Shailpreet Kaur; Aggarwal, Anju; Jairath, Mohan (International Journal of Research in Medical Sciences, 2021)
Background: Pregnancy is an immune-compromised condition; encompass physiological changes that make the women more vulnerable to infections such as COVID-19. The major concern is about the intrauterine transmission resulting in fetal and neonatal outcomes; therefore, this group of population requires more attention pertaining prevention, management and treatment. Thus, the main aim of the study is to analyze clinical characteristics among pregnant women. Methods: The study was conducted on 17092 samples of pregnant adults whose nasopharyngeal and/or oropharyngeal swab samples were received from various districts of Punjab (Amritsar, Gurdaspur, Hoshiarpur, Kapurthala, Tarn Taran and Pathankot) from the period of March 2020 to December 2020. Confirmation of SAS-CoV-2 was done by RT-PCR. Results: Out of total samples (17092), 374 (2.19%) females exhibited positive results for SARS-CoV-2, and mean age of the pregnant females was 26.37 years. Analysis was performed on 210 (Positive) samples as cases and 210 age matched control females (SARS-CoV-2 negative). Analysis performed demonstrated that SpO2 <96% and co-morbidities such as diabetes and hypertension showed significant association and are common factors in COVID-19. None of the case showed any neonatal and maternal demise. Conclusions: In the present study, saturation level of oxygen (<96%), diabetes and hypertension was found to be significant. All the pregnant women have similar symptoms as that of non pregnant adults.